Factors influencing the performance of cardiopulmonary resuscitation by lay rescuers: A qualitative study based on the Theory of Planned Behavior. - Zhikang Zhong; Weiwei Li; Lin Zhou; Liang Liu (PLoS ONE)
Aims This study investigated the underlying causes for the current low rate of cardiopulmonary resuscitation (CPR) implementation among lay rescuers. Specifically, the study aimed to identify the factors that influence both the intention to perform CPR and the subsequent translation of this intention into actual behavior. The ultimate goal was to propose strategies to significantly enhance the rate of bystander CPR. Methods A qualitative study employing purposive sampling was undertaken, with semi-structured interviews conducted between January 1, 2022, and May 20, 2022. The collected data were analyzed thematically using Nvivo software. Results A total of 29 lay rescuers participated in this study, and 11 thematic categories were identified across the four constructs of the Theory of Planned Behavior (TPB). Within the domain of attitudes, two primary themes emerged, each comprising two subthemes: (1) Emotional resistance to the death event and (2) recognition of the potential benefits of rescue, including the prospect of external rewards and the realization of intrinsic self-worth. For perceived norms, three themes were identified: (1) The bystander effect, (2) the encouraging influence of peers, and (3) personal motivation arising from one's career. With respect to perceived behavioral control (PBC), three themes and two subthemes emerged: (1) Consideration of potential consequences, encompassing concerns about legal disputes and the fear of disease transmission; (2) the dual impact of public opinion pressure; (3) low self-efficacy. Finally, in relation to actual control, three themes and two subthemes were demonstrated: (1) Acquisition of CPR skills; (2) the influence of situational factors at the scene, including both supportive elements such as public facilities or procedures and obstructive factors, such as a diminished sense of responsibility at specific locations; (3) the impact of the patient's condition. Conclusions This study extends the TPB in the context of bystander CPR interventions by (1) integrating both emotional (death anxiety) and cognitive dimensions of attitude formation under stress, (2) reconceptualizing PBC as context-dependent, influenced by legal risks and automated external defibrillator (AED) accessibility, and (3) addressing the tension between the bystander effect and moral obligation through normative adjustments. To improve intervention rates, it is crucial to target emotional barriers (virtual reality (VR)-based anxiety reduction) and address systemic constraints (AED availability and simplified Good Samaritan laws) while leveraging artificial intelligence tools to reinforce positive norms. Future work is encouraged to validate the model's cross-cultural applicability and assess interventions such as community AED programs and VR training aimed at bridging the gap between bystander hesitation and timely CPR delivery.